EHealth marketing to millennials: a view through a systemigram. (2017) - Prybutok, Gayle; Harun, Ahasan; Prybutok, Victor
With the help of Boardman soft systems methodology (BSSM) and its associated graphical system technique (i.e., systemigram), this work seeks to improve identification and comprehension of the intricate relationships between the factors that impact the millennial eHealth marketing landscape. This study contributes to the literature by: a) pinpointing the bottlenecks in the domain of millennial eHealth marketing; b) providing practitioners and academics with a detailed graphical representation of the circumstances they are facing; c) providing system analysts with relevant information for better comprehension of the systemic issues concerning millennial eHealth marketing; d) providing important insights that illuminate new avenues to explore through the medium of the systemigram. Further outcomes of these findings and implications for future research are elaborated.